Putting coastal communities at the center of a sustainable blue economy: A review of risks, opportunities, and strategies - Evans, Louisa S.; Buchan, Pamela M.; Fortnam, Matt; Honig, Maria; Heaps, Louise (Frontiers in Political Science, 2023)
New approaches to ocean governance for coastal communities are needed. With few exceptions, the status quo does not meet the diverse development aspirations of coastal communities or ensure healthy oceans for current and future generations. The blue economy is expected to grow to USD2.5–3 trillion by 2030, and there is particular interest in its potential to alleviate poverty in Least Developed Countries and Small Island Developing States, and to support a blue recovery from the COVID-19 pandemic. This paper presents a selective, thematic review of the blue economy literature to examine: (i) the opportunities and risks for coastal communities, (ii) the barriers and enablers that shape community engagement, and (iii) the strategies employed by communities and supporting organizations, which can be strengthened to deliver a ‘sustainable' blue economy and improve social justice for coastal communities. Our review finds that under business-as-usual and blue growth, industrial fisheries, large-scale aquaculture, land reclamation, mining, and oil and gas raise red flags for communities and marine ecosystems. Whereas, if managed sustainably, small-scale fisheries, coastal aquaculture, seaweed farming and eco-tourism are the most likely to deliver benefits to communities. Yet, these are also the sectors most vulnerable to negative and cumulative impacts from other sectors. Based on our evaluation of enablers, barriers and strategies, the paper argues that putting coastal communities at the center of a clear vision for an inclusive Sustainable Blue Economy and co-developing a shared and accessible language for communities, practitioners and policy-makers is essential for a more equitable ocean economy, alongside mainstreaming social justice principles and integrated governance that can bridge different scales of action and opportunity.